Alternative energies. Updates on progress. - (:unkn) unknown (Springer, 2013)
This book presents twelve chapters based on fundamental and applied research of alternative energies. At the present time, the challenge is that technology has to come up with solutions that can provide environmentally friendly energy supply options that are able to cover the current world energy demand. Experts around the world are working on these issues for providing new solutions that will break the existing technological barriers. This book aims to address key pillars in the alternative energy field, such as: biomass energy, hydrogen energy, solar energy, wind energy, hydroelectric power, geothermal energy and their environmental implications, with the most updated progress for each pillar. It also includes the life cycle assessment (LCA) and thermoeconomic analysis (TA) as tools for evaluating and optimising environmental and cost subjects. Chapters are organized into fundamental research, applied research and future trends.
Keywords: Alternativenergie; Biomasse; Biogas; Wasserkraft; Abfallverwertung; Windenergieanlage; Sonnenenergie; Umweltverträglichkeit; Energiepflanze; Lebenszyklus; Thermische Abfallbehandlung; Thermische Verwertung; Brennstoffzelle